Antioxidant Activity of Black Turmeric Rhizome (Curcuma caesia Roxb.) Extract Using DPPH Radical Scavenging Assay - Andi Muflihunna; Rahmawati Rahmawati; Nurul Rahmah (Universitas Muslim Indonesia, 2026)
Free radicals are highly reactive molecules that contribute to the development of various diseases, particularly degenerative disorders such as cancer, cardiovascular diseases, and aging-related conditions. Antioxidants play a crucial role in neutralizing free radicals and preventing oxidative damage. Black turmeric (Curcuma caesia Roxb.) is a medicinal plant widely used in traditional medicine and is known for its rich content of bioactive compounds, including alkaloids, flavonoids, phenolics, curcuminoids, terpenoids, tannins, and proteins, which contribute to its therapeutic potential. This study aimed to evaluate the antioxidant activity of ethanol extracts of black turmeric rhizomes using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method, with a comparison of different extraction techniques. The extracts were obtained using maceration and water bath-assisted maceration methods with 96% ethanol as the solvent. Antioxidant activity was expressed in terms of the half-maximal inhibitory concentration (IC₅₀). The results demonstrated that the extraction method significantly influenced antioxidant activity. The maceration method yielded an IC₅₀ value of 9.2503 µg/mL, indicating very strong antioxidant activity (10 µg/mL). In contrast, the water bath-assisted maceration method produced an IC₅₀ value of 12.9274 µg/mL, which falls within the strong antioxidant category (10–50 µg/mL). In conclusion, black turmeric (Curcuma caesia Roxb.) rhizome extract exhibits potent antioxidant activity, with the maceration method providing superior results compared to water bath-assisted maceration. These findings suggest that black turmeric has significant potential as a natural antioxidant source and that extraction methods play a critical role in optimizing its bioactive properties.